Green bonds and traditional and emerging investments: Understanding connectedness during crises - Xu, D.; Hu, Y.; Corbet, S.; Hou, Y.; Oxley, Leslie (Elsevier, 2024)
This paper investigates dynamic connectedness between US green bonds and major implied volatility indices from stock, crude oil, gold, exchange rate and cryptocurrency markets through the application of a novel TVP-VAR frequency connectedness approach of Chatziantoniou et al. (2023) for the first time. The specific goal of this paper is to explore how uncertainty from different financial markets could affect the US green bonds during three major events that resulted in substantial financial market instability, such as the US–China trade war, the COVID-19 pandemic, and the Russia–Ukraine conflict. Firstly, there is a relatively low connectedness between green bonds and all implied volatility indices. Secondly, the degree of transmission is notably influenced by such extreme events. Thirdly, the US green bond market is a receiver of each of the analysed stock, oil, and gold markets, while it is a transmitter of exchange rate and cryptocurrency markets. Fourthly, the US green bond functioned as the primary shock transmitter for the cryptocurrency market during the COVID-19 outbreak, but it shifted to being a receiver of shocks during the Russia–Ukraine conflict. Lastly, connectedness between the green bond market and other financial markets is predominantly driven by short-term frequencies. Our results are crucial for understanding the evolution of green bonds, especially during turbulent periods, and assessing green bonds’ classification as safe assets. Such findings also show that black swan events have been deeply disruptive to the green transition, with specific relevance to policymakers and market participants.